2021
DOI: 10.3390/nu13030886
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between the Gut Microbiome and the Immune System in the Context of Infectious Diseases throughout Life and the Role of Nutrition in Optimizing Treatment Strategies

Abstract: Infectious diseases and infections remain a leading cause of death in low-income countries and a major risk to vulnerable groups, such as infants and the elderly. The immune system plays a crucial role in the susceptibility, persistence, and clearance of these infections. With 70–80% of immune cells being present in the gut, there is an intricate interplay between the intestinal microbiota, the intestinal epithelial layer, and the local mucosal immune system. In addition to the local mucosal immune responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(123 citation statements)
references
References 124 publications
0
122
0
1
Order By: Relevance
“…Also, there is a positive relationship between the integrity of gut microbiota and local, innate, and systemic immunity ( Wiertsema et al, 2021 ). Microbiota profile was positively modified by exercise intervention ( Quiroga et al, 2020 ).…”
Section: Anti-inflammatory Signaling Pathways Of Moderate Intensity Exercisementioning
confidence: 99%
“…Also, there is a positive relationship between the integrity of gut microbiota and local, innate, and systemic immunity ( Wiertsema et al, 2021 ). Microbiota profile was positively modified by exercise intervention ( Quiroga et al, 2020 ).…”
Section: Anti-inflammatory Signaling Pathways Of Moderate Intensity Exercisementioning
confidence: 99%
“…Human existence is essentially dependent on the action of microorganisms, as they play fundamental roles in the fixation of nitrogen, production of vitamins, photosynthesis, and decomposition of organic matter [ 1 , 2 , 3 ]. Nonetheless, a shift of the delicate balance between the immune system and microorganisms in favor of the latter could cause severe immunodeficiencies [ 2 , 4 ]. Accounting for millions of deaths each year worldwide, infectious diseases, which are caused by pathogenic bacteria, viruses, fungi, or parasites and can be directly or indirectly transmitted through air, water, food, or living vectors, have become a challenging threat to public health and a top priority area for health policy [ 2 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study align with their studies, as we also found an increasing trend in the population of these bacteria. Microbiota is an integral part of the defense mechanism of the host, helping to prevent or reduce viral infection by regulating immune response [ 20 ], but viral infection can also alter the microbiota composition of the host and further influence the infectivity [ 21 ]. The findings of our study imply that the nasal microbiota composition of patients might have undergone some alterations in response to COVID-19 infection, or patients with above mentioned bacterial taxa are more susceptible to COVID-19 infections.…”
Section: Resultsmentioning
confidence: 99%